Download as pdf or txt
Download as pdf or txt
You are on page 1of 4

SECTION 4.

5 OF DEVLIN

Composition.
Definition. If f : A → B and g : B → C, the composition of g and f is the function
g ◦ f : A → C defined by
(g ◦ f )(x) = g(f (x)).
Theorem. Let f : A → B, g : B → C, and h : C → D. Then
(h ◦ g) ◦ f = h ◦ (g ◦ f ).

(exercise)
Theorem. If f : A → B, then
IB ◦ f = f ◦ IA = f.

(exercise)
Theorem. Let f : A → B and g : B → C.
1. If f and g are 1-1, then g ◦ f is 1-1.
2. If g ◦ f is 1-1, then f is 1-1.
3. If f and g are onto, then g ◦ f is onto.
4. If g ◦ f is onto, then g is onto.

(1, 3, and 4 are exercises)

Proof of 2. Assume that g ◦ f is 1-1. Let x, y ∈ A, and assume that x 6= y. Since g ◦ f is 1-1,
we have g ◦ f (x) 6= g ◦ f (y), hence g(f (x)) 6= g(f (y)). Thus we have f (x) 6= f (y). Therefore
f is 1-1. 

Inverses.
Definition. f : A → B is invertible if there exists g : B → A such that for all x ∈ A and
y ∈ B we have
f (x) = y ⇐⇒ x = g(y),
in which case g is an inverse of f .
Theorem. g : B → A is an inverse of f if and only if both of the following are satisfied: for
all x ∈ A we have g(f (x)) = x, and for all y ∈ B we have f (g(y)) = y.
1
2 SECTION 4.5 OF DEVLIN

Proof. First assume g is an inverse of f .

Let x ∈ A. Put y = f (x). Then g(y) = x since g is an inverse of f . Thus g(f (x)) = x.
Therefore, for all x ∈ A we have g(f (x)) = x.

Let y ∈ B. Put x = g(y). Then f (x) = y since g is an inverse of f . Thus f (g(y)) = y.


Therefore, for all y ∈ B we have f (g(y)) = y.

Conversely, assume the conditions involving g(f (x)) and f (g(y)).

Let x ∈ A and y ∈ B. Suppose f (x) = y. Then

g(y) = g(f (x)) = x.

Similarly, if g(y) = x, then


f (x) = f (g(y)) = y.
Therefore g is an inverse of f . 

Corollary. If f : A → B and g : B → A, then g is an inverse of f if and only if both

g ◦ f = IA and f ◦ g = IB .

(exercise)

Theorem. If g, h : B → A are both inverses of f : A → B, then g = h.

Proof. We have
g = g ◦ IB = g ◦ (f ◦ h) = (g ◦ f ) ◦ h = IA ◦ h = h. 

Definition. If f is invertible, the unique inverse of f is written f −1 .

Theorem. f : A → B is invertible if and only if it is bijective.

Proof. First assume that f is invertible. Then f is 1-1 becuase f −1 ◦ f = IB is, and f is onto
because f ◦ f −1 = IA is. Thus f is bijective.

Conversely, assume that f is bijective. Define g : B → A as follows: for each y ∈ B, let g(y)
be the unique x ∈ A such that f (x) = y. Then for all x ∈ A and y ∈ B we have

f (x) = y ⇐⇒ x = g(y),

so f is invertible. 
SECTION 4.5 OF DEVLIN 3

Back and forth.


Theorem. Let f : A → B.
1. For all C ⊆ A we have C ⊆ f −1 (f (C)).
2. f is 1-1 if and only if for all C ⊆ A we have f −1 (f (C)) = C.
3. For all D ⊆ B we have f (f −1 (D)) ⊆ D.
4. f is onto if and only if for all D ⊆ B we have f (f −1 (D)) = D.

Proof. 1. Let C ⊆ A. Let x ∈ C. Then f (x) ∈ f (C). Thus x ∈ f −1 (f (C)). Therefore


C ⊆ f −1 (f (C)).
2. First assume that f is 1-1. Let C ⊆ A. Let x ∈ f −1 (f (C)). Then f (x) ∈ f (C). Thus
we can choose y ∈ C such that f (x) = f (y). Since f is 1-1, we have x = y. Thus x ∈ C.
Therefore f −1 (f (C)) ⊆ C. From Part 1 we know that C ⊆ f −1 (f (C)). Thus f −1 (f (C)) = C.
Conversely, assume that for all C ⊆ A we have f −1 (f (C)) = C. Let x, y ∈ A, and suppose
f (x) = f (y). Put C = {y}. Then f (C) = {f (y)}. Since f (x) = f (y), we have f (x) ∈ f (C),
hence x ∈ f −1 (f (C)). Thus x ∈ C, so we have x = y. Therefore f is 1-1.
3. Let D ⊆ B. Let y ∈ f (f −1 (D)). Then we can choose x ∈ f −1 (D) such that y = f (x).
We also have f (x) ∈ D. Thus y ∈ D. Therefore f (f −1 (D)) ⊆ D.
4. First assume that f is onto. Let D ⊆ B. Let y ∈ D. We can choose x ∈ A such that
f (x) = y. Thus f (x) ∈ D, so x ∈ f −1 (D). Hence y ∈ f (f −1 (D)). Therefore D ⊆ f (f −1 (D)).
From Part 3 we know that f (f −1 (D)) ⊆ D. Thus f (f −1 (D)) = D.
Conversely, assume that for all D ⊆ B we have f (f −1 (D)) = D. Let y ∈ B. Put D = {y}.
Then y ∈ f (f −1 (D)), so there exists x ∈ f −1 (D) such that y = f (x). Hence y ∈ f (A).
Therefore f is onto. 

Functions and families of sets.


Theorem. Let f : A → B, and let {Ci | i ∈ I} be a family of subsets of A. Then:
S S
1. f (Ti∈I Ci ) = Ti∈I f (Ci ), and
2. f ( i∈I Ci ) ⊆ i∈I f (Ci ).
S S
Proof. 1. Let y ∈ f ( i∈I Ci ). We can choose x ∈ i∈I Ci such thatS y = f (x). Then we
∈ I such that x ∈ Ci . Hence y ∈ f (Ci ). Thus y ∈ i∈I f (Ci ). Therefore
canS choose i S
f ( i∈I Ci ) ⊆ i∈I f (Ci ).
S
Let y ∈ i∈I f (Ci ). We can choose i S ∈ I such that y ∈ fS(Ci ). Then we can choose S x ∈ Ci
such
S that y = f (x). We have x ∈ C
i∈I i , so y ∈ f ( C
i∈I i ). Therefore i∈I f (Ci) ⊆
f ( i∈I Ci ).
S S S S S S
Since f ( i∈I Ci ) ⊆ i∈I f (Ci ) and i∈I f (Ci ) ⊆ f ( i∈I Ci ), we have f ( i∈I Ci ) = i∈I f (Ci ).
4 SECTION 4.5 OF DEVLIN
T T
2. Let y ∈ f ( i∈I Ci ). We can choose x ∈
T i∈I Ci such that y = fT(x). Then T for all i ∈ I we
have x ∈ Ci , hence y ∈ f (Ci ). Thus y ∈ i∈I f (Ci ). Therefore f ( i∈I Ci ) ⊆ i∈I f (Ci ). 
Theorem. Let f : A → B, and let {Di | i ∈ I} be a family of subsets of B. Then:
1. f −1 (Ti∈I Di ) = Ti∈I f −1 (Di ), and
S S
2. f −1 ( i∈I Di ) = i∈I f −1 (Di ).

Proof. 1. Let x ∈ A. Then:


[ [
x ∈ f −1 ( Di ) ⇐⇒ f (x) ∈ Di
i∈I i∈I
⇐⇒ (∃i ∈ I)f (x) ∈ Di
⇐⇒ (∃i ∈ I)x ∈ f −1 (Di )
[
⇐⇒ x ∈ f −1 (Di ).
i∈I

2. Let x ∈ A. Then:
\ \
x ∈ f −1 ( Di ) ⇐⇒ f (x) ∈ Di
i∈I i∈I
⇐⇒ (∀i ∈ I)f (x) ∈ Di
⇐⇒ (∀i ∈ I)x ∈ f −1 (Di )
\
⇐⇒ x ∈ f −1 (Di ). 
i∈I

Theorem. Let f : A → B, and let D ⊆ B. Then


f −1 (D0 ) = (f −1 (D))0 ,
where
D0 = B − D and (f −1 (D))0 = A − f −1 (D).

Proof. Let x ∈ A. Then:


x ∈ f −1 (D0 ) ⇐⇒ f (x) ∈ D0
⇐⇒ f (x) ∈
/D
/ f −1 (D)
⇐⇒ x ∈
⇐⇒ x ∈ (f −1 (D))0 . 

You might also like